2012
DOI: 10.1371/journal.pone.0044498
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of the Pimelic Diphenylamide HDAC Inhibitor HDACi 4b Is Unsuitable for Chronic Inhibition of HDAC Activity in the CNS In Vivo

Abstract: Histone deacetylase (HDAC) inhibitors have received considerable attention as potential therapeutics for a variety of cancers and neurological disorders. Recent publications on a class of pimelic diphenylamide HDAC inhibitors have highlighted their promise in the treatment of the neurodegenerative diseases Friedreich’s ataxia and Huntington’s disease, based on efficacy in cell and mouse models. These studies’ authors have proposed that the unique action of these compounds compared to hydroxamic acid-based HDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 44 publications
4
46
0
Order By: Relevance
“…HDACi 4b was dissolved with 75% (vol/vol) polyethylene glycol 200; control mice received double-distilled H 2 O containing an equal volume of drug vehicle. Our previous studies have found that the s.c. injection paradigm for HDACi 4b is optimal for improving disease phenotypes in N171-82Q transgenic mice, given the poor solubility of HDACi 4b for drinking water paradigms (44,45).…”
Section: Methodsmentioning
confidence: 99%
“…HDACi 4b was dissolved with 75% (vol/vol) polyethylene glycol 200; control mice received double-distilled H 2 O containing an equal volume of drug vehicle. Our previous studies have found that the s.c. injection paradigm for HDACi 4b is optimal for improving disease phenotypes in N171-82Q transgenic mice, given the poor solubility of HDACi 4b for drinking water paradigms (44,45).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of RGFP136 recapitulated the behavioral effects that were observed in HDAC3 f loxed C57BL/6 mice. However, reports examining the stability and pharmacokinetic properties of this class of compounds have raised concerns about the applicability of these compounds in model systems of disease [57]. More recently, Repligen Corp. has reported a series of heterocinnamyl linked ortho-aminoanilides, RGFP966, that display high selectivity for HDAC3 (FiguRe 8).…”
Section: Key Termmentioning
confidence: 99%
“…Moreover, a recent publication has questioned the use of oral administration of the HDACI 4b in vivo in mouse models [134]. These authors demonstrated that based on physicochemical properties, metabolic and p-glycoprotein substrate liability, the compound 4b, is suboptimal to investigate inhibition in vivo in mouse models using oral administration [134].…”
Section: Role Of Hdac Inhibitors In Huntington's Disease-preclinical mentioning
confidence: 99%
“…These authors demonstrated that based on physicochemical properties, metabolic and p-glycoprotein substrate liability, the compound 4b, is suboptimal to investigate inhibition in vivo in mouse models using oral administration [134]. Undoubtedly, more studies have to be performed using other methods of delivery as well as assessing effects in more slowly progressing HD models to better evaluate the effects of this HDAC inhibitor.…”
Section: Role Of Hdac Inhibitors In Huntington's Disease-preclinical mentioning
confidence: 99%